An overview of cultural and media literacy theory - Li, Li; Hj Mohammad Razi, Siti Aishah; Yaakup, Hani Salwah (Human Resource Management Academic Research Society, 2023)
Media literacy has long been of great interest to scholars in the field of communication, and the related topics mainly focus on the impact of media information on individuals and society. With the continuous development and evolution of media technology, media literacy has also gained new entry points for research. The Internet's characteristic of breaking geographical and time constraints brings opportunities as well as challenges to minority groups and their cultures. Minority groups are minorities in the statistical sense of the word, as well as politically, economically, and culturally disadvantaged groups. However, the existence of minority cultures makes cultural diversity in the world possible. China, as a multiethnic country with many minorities, has also achieved a rich and diverse culture. The development of Internet technology and the popularization of social media have made it easier for minority groups to access the Internet and have made it possible for minority groups to make their voices heard and to disseminate and record their cultures. But participating in the culture of the digital realm is no longer a matter of access, but a matter of using skills. Therefore, it is of great significance to improve the media literacy of ethnic minority groups so that they can use the media for their own purposes and further enhance the positive impact of social media.